Epiplatys atratus (Cyprinodontiformes: Nothobranchiidae), a new species of the E. multifasciatus species group from the Lulua Basin (Kasaï drainage), Democratic Republic of Congo - Zee, Jouke R. Van Der; Munene, José J. Mbimbi Mayi; Sonnenberg, Rainer (Zootaxa, 2013)
Epiplatys atratus, a new species of the E. multifasciatus group, is described from specimens collected from several tributaries of the middle Lulua River, a tributary of the Kasaï River, south of Kananga (Democratic Republic of the Congo, Kasaï Occidental Province). Epiplatys atratus is the south-eastern most representative of the genus. Large adult E. atratus males differ from all congeners in displaying a dark grey to black pigmentation of body and fins. In contrast to other Epiplatys species, with a fully exposed laterosensory system of the head, the lobes surrounding the supra-orbital part of the laterosensory system almost completely cover the system in large males of E. atratus. Also in males of E. atratus the dorsal fin is positioned on average more anteriorly than in other members of the E. multifasciatus group. Small males and females show a unique pattern of three fine oblique dark bars just behind the pectoral fin.